2017
DOI: 10.1080/02699931.2017.1284044
|View full text |Cite
|
Sign up to set email alerts
|

Of guns and snakes: testing a modern threat superiority effect

Abstract: Previous studies suggest that ancient (i.e. evolutionary-based) threats capture attention because human beings possess an inborn module shaped by evolution and dedicated to their detection. An alternative account proposes that a key feature predicting whether a stimulus will capture attention is its relevance rather than its ontology (i.e. phylogenetic or ontogenetic threat). Within this framework, the present research deals with the attentional capture by threats commonly encountered in our urban environment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…Taken the above findings together, it seems to be that the confound and mixed results of previous experiments using the VST, as previous research (Quinlan, 2013; Quinlan et al, 2017; Subra et al, 2017) pointed out, could possibly originate from a pop-out effect, i.e., the interaction between the context and different subtypes of target stimuli. In conclusion, the results of our first experiment suggest a relevance superiority effect (Sander et al, 2003, 2005; Fox et al, 2007; Brown et al, 2010; Subra et al, 2017; Zsido et al, 2018a) over the evolutionary fear-module (Öhman et al, 2001; Mineka and Öhman, 2002; Öhman and Mineka, 2003), i.e., threatening targets are found faster compared to neutral targets regardless of their evolutionary relevance. Nevertheless, it must be noted that the current behavioral results say little about the underlying mechanisms that might be different for the evolutionary and modern threatening stimuli (Fang et al, 2016; Zsido et al, 2018c).…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Taken the above findings together, it seems to be that the confound and mixed results of previous experiments using the VST, as previous research (Quinlan, 2013; Quinlan et al, 2017; Subra et al, 2017) pointed out, could possibly originate from a pop-out effect, i.e., the interaction between the context and different subtypes of target stimuli. In conclusion, the results of our first experiment suggest a relevance superiority effect (Sander et al, 2003, 2005; Fox et al, 2007; Brown et al, 2010; Subra et al, 2017; Zsido et al, 2018a) over the evolutionary fear-module (Öhman et al, 2001; Mineka and Öhman, 2002; Öhman and Mineka, 2003), i.e., threatening targets are found faster compared to neutral targets regardless of their evolutionary relevance. Nevertheless, it must be noted that the current behavioral results say little about the underlying mechanisms that might be different for the evolutionary and modern threatening stimuli (Fang et al, 2016; Zsido et al, 2018c).…”
Section: Discussionmentioning
confidence: 50%
“…Consequently, an alternative theory was proposed, namely, the relevance superiority effect (Sander et al, 2003, 2005; Fox et al, 2007; Subra et al, 2017; Zsido et al, 2018a, c). The relevance superiority effect suggests that people perceive fear-relevant – threatening in this context – stimuli faster than neutral ones regardless of evolutionary relevance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown (see e.g. Subra et al, 2018; Zsido et al, 2018a) using various paradigms that a modern threatening stimulus could lead to similar behavior as an evolutionary relevant one. For instance, when modern (e.g., gun) and evolutionary (e.g., snake) targets are compared directly in the classical visual search task proposed by Öhman and colleagues (see e.g., Öhman et al, 2001), the modern threatening target caught participants attention faster than evolutionary ones (Zsido et al, 2018b).…”
Section: Data Incompatible With Modular Theoriesmentioning
confidence: 99%